The Isolation of Lead-Tolerant PGPR from Red Clover Soil and Its Role in Promoting the Growth of Alfalfa - Wanting Nie; Yuchen Wu; Jingwen Jiang; Zicheng Wang; Meiqi Mu; Siwen Zhao; Minghao Yang; Xi Long; Xiujie Yin; Xiaohua Teng (Microorganisms)
Alfalfa (Medicago sativa L.) is an outstanding species used for the remediation of heavy metal-contaminated soil, and our previous research has shown that PGPR can promote plant growth under high-concentration lead stress. This discovery has forced scientists to search for PGPR strains compatible with alfalfa to develop an innovative bioremediation strategy for the remediation of lead-contaminated soil. This study used lead-tolerant rhizosphere soil of red clover as experimental material; cultured, isolated, and screened 52 excellent lead-tolerant bacteria that promote rhizosphere growth; and then inoculated them into alfalfa. Marked differences existed in the secretion of auxin, protease, and ACC deaminase among these strains. The results indicated that Pseudomonas spp. (strain Y2), Pseudomonas spp. (strain Y22), and Bacillus spp. (strain Y23) exhibited a strong growth-promoting ability in alfalfa, and there was no antagonistic reaction among the three strains, enabling their coexistence. The pot experiment manifested that strains Y2, Y22, Y23, and YH (a mixture of Y2, Y22, and Y23) could increase the plant height, root length, fresh and dry weight above ground, and fresh and dry weight below ground of alfalfa. They could all significantly raise the chlorophyll content and antioxidant enzyme activity in alfalfa (p < 0.05) and the content of malondialdehyde (MDA) in alfalfa. Furthermore, the concurrent inoculation of three distinct types of plant growth-promoting rhizobacteria (PGPR) significantly diminished lead (Pb) concentrations in rhizosphere soil, enhanced the levels of available potassium (AK) and available phosphorus (AP), and augmented the capacity of plants to absorb Pb. The results imply that PGPR can be employed to facilitate plant growth and microbial-assisted remediation of lead and other heavy metal-contaminated soil and establish a basis for further research on the growth-promoting mechanism of PGPR in plants.